Fostering Mental Health and Well-Being among Hajj Pirlgrims: A Narrative Review - Yusuf, Moh; Ramadlani, Luthfia Wahyu; Airlangga, Moch. Mega (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v3i0.3756, 2026)
Indonesia is one of the countries with the largest muslim population in the world, with a Hajj pilgrim quota of approximately 221,000 people for the 2022-2025 period. Hajj worship require not only physical strength but also good mental health and well-being. Adjusting to a new environment and culture can trigger anxiety, stress, homesickness, and even psychosomatic symptoms, which will affect the mental health of Hajj pilgrims. This study aims to develop strategies that can improve the mental health and well-being of Hajj pilgrims. This study is a narrative review of related literature describing the mental health and well-being of Hajj pilgrims.This paper summarizes available evidence from various literatures on factors influencing the mental health of Hajj pilgrims. Based on the analysis of various literatures, a strategic framework can be developed, including psychological training on mental readiness, stress management, and counseling, as well as effective interventions to improve the mental health and well-being of Hajj pilgrims.